Marketing stratégia a szelíd turizmus szolgálatában a Mura Régió ETT-ben - Lóránt, Bali; János, Csapó (Közép-Európai Közlemények, 2021)
As an association of local governments, the Regional Development Association of Nationalities Along the Mura (Muramenti Nemzetiségi Területfejlesztési Társulás) made significant contribution in order to develop the region along the Mura where both Croatians and Hungarians inhabit the area. The experiences of the last 25 years were based on confidence. This accumulated social capital resulted in the creation of the Mura Region EGTC with the participation of the Croatian Donja Dubrava, Donji Vidovec and Gorican which will eventuate a quality change in terms of regional development and especially concerning tourism. The EGTC functions as a quasi-enterprise, acquiring legal status and so besides the national tender sources it can be candidated directly to the sources of the European Union. The uniqueness of this association is provided by the fact that, unlike in the Carpathian Basin where usually the Hungarian-Hungarian relations are dominating, in this case the Croatian-Croatian connections are characteristic. The Mura Region provides unique natural environment and a rather complex potential for tourism (Csapó 2014). Unfortunately the quantity and quality of the infrastructure demands further investments to satisfy the different needs of the tourists. Creating a good relationship for cooperation and permanent search for financial resources are essential tasks for local governments. The researched area is a border region of Hungary with unique social relations where not Hungarian-Hungarian but Croatian-Croatian relations are dominating. In addition, size and existing daily inter-ethnic relations contribute to the high level of success.